EFFECT OF FEEDING DETOXIFIED CASTORSEED CAKE IN LACTATING BUFFALOES - S. R. Bhagwat; S. Parnerkar; Sanjay B. Patil (Journal of Animal and Plant Sciences, 2012)
An on farm trial of 15 days preliminary feeding and 75 days experimental period was conducted in Palanpur taluka of Banaskantha District on sixteen Mehsani lactating buffaloes. The buffaloes were randomly assigned to two dietary treatments control (T1) and 10 % detoxified (Lime treated and extrusion cooked) castor cake based concentrate mixture (T2) and green and dry fodder. The milk yield of morning and evening milking of individual animal was recorded daily and was compiled for five periods of 15 days each. At the end of experimental period, a digestion trial of 7 day collection was undertaken. The average daily dry matter intake of experimental buffaloes in T1 and T2 groups during digestion trial was 3.05 ± 0.11and 3.39 ±0.16 Kg/100 Kg Body Weight were statistically similar. The average content of DCP (7.94 ±0.37 and 8.02 ± 0.24 %) and TDN (65.06±0.97 and 65.91± 1.42 %) were also statistically similar in T1 and T2 groups, respectively. The average fortnightly yield of whole milk in T1 and T2 groups was 135.01± 1.63 and 137.38 ± 0.74 Kg respectively and was statistically similar. The gross milk composition of T1 and T2 groups in terms of fat (8.36±0.21 and 8.55 ± 0.13%) and SNF (8.83 ± 0.17 and 10.17 ± 0.11%), respectively was statistically similar. The fortnightly and cumulative yield of FCM 171.70±0.5.16and 177.89±0.2.67; 1001.25±54.02 and 1047.59±88.72 kg/head respectively were statistically similar. The feed conversion efficiency in terms of DM, DCP and TDN intake (Kg/Kg milk, Kg/Kg FCM and Kg/Kg SCM) were statistically similar. The daily feed cost (Rs/head/day) was Rs.74.88±0.79 in control group which was significantly higher than the CCK based ration (Rs.68.89±3.05). The return as % of feed cost (170.68±3.03 in control and 194.93±7.91 in treatment group) was significantly higher in CCK group.
Keywords: NA